THE IMPACT ANALYSIS OF RISING FOOD PRICES ON FARMER’S WELFARE IN EAST JAVA - Rodhiah Umaroh; Riska Dwi Astuti; Edy Purwanto (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2019)
Agriculture is one of the important contributor sectors to the implementation of sustainable economic growth, especially in East Java. Apart from absorbing a large portion of the workforce, agriculture is also a sector that drives other sectors such as trade, especially for food products. However, the increase in food prices is often a polemic in the community which is very detrimental to households. This study aims to analyze the function of household food consumption demand in East Java using the Quadratic Almost Ideal Demand System (QUAIDS) and Compensating Variation approaches to identify the impact of price changes on changes in household welfare in East Java, especially in farmer households. The data used in this study were obtained from the Indonesian Family Life Survey (IFLS) in 2000, 2007, and 2014. The results showed that consumption of various food commodities in the form of staple foods, fruits and vegetables, sugar, oil, milk, meat will be greatly affected by changes in prices, expenditure/income, and household demographic characteristics. The results of price and expenditure elasticity vary between household groups. Based on the analysis of changes in welfare, due to the increase in food prices, in general, households in East Java will experience a decrease in welfare. However, the decline for poor rural households and farming households is lower than for urban poor households and non-farmer households. The regional government of East Java province is expected to encourage and optimize the role of the agricultural sector to achieve sustainable household welfare in general and farmers in particular. JEL: D11, D60, E31, Q11